An Inquiry into Vietnam Buddhist Higher Education System with special reference to Vietnam Buddhist University in Hue - Khanh, Lai Quoc (The Journal of International Association of Buddhist Universities (JIABU), 2020)
The young play a vital role in the development of each country in the world, so moral education for this group of people has been attracted great interest. There is a fact that the young’s ethics now show some negative points; hence, the study of Loving-kindness and Compassion in Buddhism has both theoretical and practical significance. This article is aimed to clearly present basic teachings about the Loving-kindness and Compassion in Buddhism and its implications into improving the ethical education for the young in Vietnam. The importance of ethical values in Buddhism to the full education for the young generation in modern society is also discussed.